Edukasi Penggunaan Alat Pelindung Diri (APD) Pelindung Jari Pada Pemilahan Sampah AMDK Gelas Plastik Di Bank Sampah SiHatin - Eko Ari Wibowo; Widyastuti; Ida Betanursanti; Galih Mahardika Munandar; Nabila Fitri Rahmawati; Widya Anggrianita Ramadhani (Pusat Riset dan Inovasi Nasional, 2024)
The increase in consumption of bottled drinking water (AMDK) reached 54.11% from 2018 to 2020, which has a negative impact on the environment. SiHatin Waste Bank is a community formed to manage the waste. Waste Bank officers face the risk of injury and infection, especially to the hands, due to the lack of Personal Protective Equipment (PPE) during the processing of plastic glass AMDK waste. This condition creates new problems for Waste Bank officers, the purpose of this activity is to implement education on the use of finger protection in sorting and cutting plastic glass AMDK. The method of implementation of the activity involves observation, preparation of educational materials, direct training at the Waste Bank location, and evaluation of the impact through monitoring changes in officer behavior. The implementation of education on the use of PPE succeeded in increasing staff understanding by 41%, which is expected to reduce the incidence of injury and infection in the process of cutting plastic bottled water. It also contributed positively to the overall operations of the Waste Bank. In the next stage, there is a need for comprehensive monitoring by involving stakeholders to support the implementation of education holistically in an effort to manage sustainable waste.